Effects of Chinese Medicine on modulating interleukin-17-regulated macrophages in coronary heart disease - Liu, Qingqing; Liu, Peizhong; Li, Chuangpeng; Zhao, Zhen; Wang, Dawei; Liu, Qing; Yang, Huawei (Frontiers in Pharmacology, 2025)
Coronary atherosclerotic heart disease (CHD) is one of the leading causes of death from cardiovascular disease worldwide and has significant inflammatory features. Macrophages play an important role in atherosclerotic plaque formation and inflammation. IL-17, as a pro-inflammatory cytokine, further exacerbates the development of CHD by interacting with macrophages. In recent years, there has been increasing evidence that traditional Chinese medicine (CM) has a wide range of applications in regulating the immune system and treating CHD. This article reviewed the role of CM in the regulation of IL-17-regulated macrophages, discussed the core components and targets of CM in the treatment of CHD, and laid a theoretical foundation for its clinical application. The results show that CM can effectively inhibit the formation of foam cells, stabilize vulnerable plaque and delay the progression of atherosclerosis by inhibiting inflammation, regulating the polarization of macrophages and promoting cholesterol outflow. In addition, CM can also regulate the expression and signaling pathway of IL-17, further inhibit inflammatory response and improve the symptoms of CHD, providing a new idea and method for the prevention and treatment of CHD.